2021
DOI: 10.1177/0044118x211053356
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional Relationships Between Cyberbystanders’ Roles, Cyberbullying Perpetration, and Justification of Violence

Abstract: Bystanders play a key role in understanding the phenomenon of cyberbullying (CB). The main aim of this study is to explore longitudinal bidirectional relationships among cyberbystanders’ reaction, CB perpetration, and CB justification. Participants were 1,105 adolescents (56.7% girls; Mage = 13.56, SD = 1.21) who answered self-reported questionnaires about CB perpetration, CB justification, and cyberbystanders’ reaction at two measurement periods spaced 8 months apart. The results showed that cyberbystanders w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…In line with past findings, our results demonstrated a positive association between reinforcing online behavior and moral disengagement, implying that those who reinforce bullying behaviors online are more likely to also report higher levels of moral disengagement. Study by Orue et al ( 2021 ) examining the different bystander role behaviors showed that those engaged in reinforcing online behavior had significantly higher cyberbullying justification scores than those who engaged in online passive bystanding behavior and defending. The study defined cyberbullying justification as ideas that maintain aggression as acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…In line with past findings, our results demonstrated a positive association between reinforcing online behavior and moral disengagement, implying that those who reinforce bullying behaviors online are more likely to also report higher levels of moral disengagement. Study by Orue et al ( 2021 ) examining the different bystander role behaviors showed that those engaged in reinforcing online behavior had significantly higher cyberbullying justification scores than those who engaged in online passive bystanding behavior and defending. The study defined cyberbullying justification as ideas that maintain aggression as acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…It seems that there is some awareness of the magnitude of violence exercised through digital spaces, but few people identify themselves as victims or perpetrators. Regarding age differences among observers, the results are heterogeneous; while some authors found that older age predicted fewer pro-aggressive bystander behaviors (Orue et al, 2021), others found the opposite (Schultze-Krumbholz et al, 2018;Van Cleemput et al, 2014), or an insignificant relationship between age and cyberbystanders' reaction (Yudes-Gómez et al, 2018).…”
Section: Gender and Age Differences In The Roles Played In Digital Sp...mentioning
confidence: 99%
“…A more incipient line of studies establishes factors that predict or explain cyberbystanders’ behavior. Orue et al (2021) found that the more adolescents justified violence, the more they reinforced the aggressor as cyberbystanders. Another survey of 1,468 adolescents found that more than a third of the participants who witnessed cyberviolence against girls and women did not intervene (Rebollo-Catalan & Mayor-Buzon, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation